Self-Assembled Gelators for Organic Electronics - Babu, Sukumaran Santhosh; Prasanthkumar, Seelam; Ajayaghosh, Ayyappanpillai (Angewandte Chemie International Edition, 2012)
Nature excels at engineering materials by using the principles of chemical synthesis and molecular self‐assembly with the help of noncovalent forces. Learning from these phenomena, scientists have been able to create a variety of self‐assembled artificial materials of different size, shapes, and properties for wide ranging applications. An area of great interest in this regard is solvent‐assisted gel formation with functional organic molecules, thus leading to one‐dimensional fibers. Such fibers have improved electronic properties and are potential soft materials for organic electronic devices, particularly in bulk heterojunction solar cells. Described herein is how molecular self‐assembly, which was originally proposed as a simple laboratory curiosity, has helped the evolution of a variety of soft functional materials useful for advanced electronic devices such as organic field‐effect transistors and organic solar cells. Highlights on some of the recent developments are discussed. All gelled together: Solvent‐assisted gelation of functional organic molecules leading to one‐dimensional fibers is an area of great interest. Recent developments in molecular self‐assembly‐assisted gelation of π systems into soft functional materials and their potential application in organic electronic devices, such as organic field‐effect transistors and organic solar cells, are reviewed (see picture).